Distinct control mechanism of fine‐grained sediments from Yellow River and Kyushu supply in the northern Okinawa Trough since the last glacial. (9th August 2017) - Zhao, Debo; Wan, Shiming; Toucanne, Samuel; Clift, Peter D.; Tada, Ryuji; Révillon, Sidonie; Kubota, Yoshimi; Zheng, Xufeng; Yu, Zhaojie; Huang, Jie; Jiang, Hanchao; Xu, Zhaokai; et al.
Abstract: High‐resolution multiproxy records, including clay minerals and Sr‐Nd‐Pb isotopes of the clay‐sized silicate fraction of sediments from IODP Site U1429 in the northern Okinawa Trough, provide reliable evidence for distinct control mechanism on fine‐grained sediments input from the Yellow River and the southern Japanese Islands to the northern Okinawa Trough since 34 ka BP. Provenance analysis indicates that the sediments were mainly derived from the Yellow River and the island of Kyushu. Since the last glacial, clay‐sized sediments transported from the Yellow River to the study site were strongly influenced by sea‐level fluctuation. During low sea‐level stage (∼34–14 ka BP), the paleo‐Yellow River mouth was positioned closer to the northern Okinawa Trough, favoring large fluvial discharge or even direct input of detrital sediments, which resulted about four times more flux of clay‐sized sediments supply to the study area as during the relatively high sea‐level stage (∼14–0 ka BP). The input of Kyushu‐derived clay‐sized sediments to the study site was mainly controlled by the Kuroshio Current and Tsushima Warm Current intensity, with increased input in phase with weakened Kuroshio Current/Tsushima Warm Current. Our study suggests that the Kuroshio Current was very likely flowed into the Okinawa Trough and thus influenced the fine‐grained sediment transport in the area throughout the last glacial and deglacial. During ∼34–11 ka BP, the Kyushu clay‐sized sediment input was mainly controlled by the Kuroshio Current. Since ∼11 ka BP, the occurrence of Tsushima Warm Current became important in influencing the Kyushu fine‐grained sediment input to the northern Okinawa Trough. Key Points: Yellow River and Kyushu Island supplied fine‐grained sediments to northern Okinawa Trough since the last 34 ka Kuroshio Current flowed into the Okinawa Trough throughout the last 34 ka Sea level and Kuroshio Current system dominated the terrigenous flux from Yellow River and Kyushu Island, respectively